Pengelolaan Program Tahfizh dalam Pembentukan Karakter Peserta didik di MI Negeri 11 Boyolali - Nasri Dini, Muhammad; Khoeriyah, Umi (Pascasarjana IAIN Kudus, 2022)
The headmaster has a very important role in the tahfizh program, for its success and able to realize the character of Islamic students. MI Negeri 11 Boyolali is one of the state madrasah that has a superior program of Tahfizh Al-Qur’an Juz 30 for all its students. The purpose of this study was to determine the management of the tahfizh program in character building of students at MI Negeri 11 Boyolali. This research is a form of qualitative descriptive approach. The research subjects were tha principal of the madrasah, the coordinator of the tahfizh program, 4 tahfizh teachers, 2 student for each class. Data collection techniques in this study using interviews, observation and documentation. The results of the study indicated that : First, overall the management of the tahfizh program for building the students character at MI Negeri 11 Boyolali has been going well, while its implementation included: (1) planning; (2) organizing; (3) direction; and (4) monitoring the tahfizh program. Second, the application of memorizing Qur’an method those have been applied are (1) the tahfizh method; (2) caption method; and (3) tartil method. Third, the supporting and inhibiting factors of the tahfizh program, the supporting factors are: (1) social environment; (2) the Qur’an provided by the madrasah for memorizing; (3) the availability of classes for tahfizh activities; and (4) there are tahfizh teachers. The inhibiting foctors are: (1) the lazy nature of students; (2) the lack of classes for tahfizh activities; and (3) lack of tahfizh teachers.